PROTECTION OF PASSENGER RIGHT IN THE EU LAW - Hanna Zawistowska (Acta Scientiarum Polonorum. Oeconomia, 2010)
The need to remove all the barriers, which restrain creation of internal market and need to strengthen consumers’ position on all these fields, on which market instruments does not provide the consumers with proper protection, underlie the creation and development of legal consumers’ protection in EU. That system consists of two groups of regulations. The first group are the regulations concerning all, or big group of consumers, regardless of purchased goods or services (horizontal regulations), the second group are regulations protecting only consumer of specific goods or services (sector regulations). As a result, legal protection system of consumers in EU is in fact the aggregation of separate, not connected regulations, which are created in order to eliminate certain sources of dangers. Harmonization of that system by issuing one single legal act (consumers code), at present stage of internal market development, is not possible. That thesis is confirmed by works, executed on EU level, aiming at creation of complex system of protection of passengers. In the article were characterized regulations, which consist on system of protection of passengers using different types of transport. On the example of carriers responsibility for cancellation, delay and refuse to transport, it has been shown, that peculiarity of different transport means will unable to do the full unification, even in the confines of one subsystem like legal protection of passengers in EU.